انعكاسات الخروج الأمريكي من الاتفاق النووي الإيراني على دول الخليج العربي - اسماعيل, عصام; سويد, عمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتعرّض هذا البحث لخروج الولايات المتحدة الأمريكية من الاتفاق النووي الإيراني وأبعاده على مختلف الدول، ويركز بشكل خاص على دول الخليج وانعكاسات هذا الحدث عليها، ويهدف للتعريف بأهمية إيران وتاريخها مع البرنامج النووي، وعلاقاتها الخارجية مع الولايات المتحدة ودول الخليج العربي قبل الاتفاق النووي، وأهم المحطات التي مر بها الاتفاق النووي ومواقف الدول منه، كما يستعرض الأسباب التي ساقتها الولايات المتحدة للخروج من الاتفاق النووي وقانونية هذا الخروج وآراء الدول حوله، كما يشير لأهم الانعكاسات السياسية والاقتصادية لخروج الولايات المتحدة من الاتفاق النووي على دول الخليج العربي، وتوصل البحث إلى العديد من النتائج، وقدم بعض التوصيات. This research is exposed to the United States of America exit from the Iranian nuclear agreement and its dimensions in various countries, and focuses in particular on the Gulf States and the repercussions of this event on them, And aims to identify the importance of Iran and its history with the nuclear program and its external relations with the United States and the Gulf countries before the nuclear agreement, And the most important stations passed by the nuclear agreement and the attitudes of the countries from it, and reviewed the reasons of the United States to exit from the nuclear agreement and the legality of this getting out and the attitudes of the countries from that, And then examine the most important political and economic implications for the US exit from the nuclear agreement on the Gulf states, and the search reached many results, and made some recommendations.